PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT ADHI KARYA DEPARTEMEN GEDUNG JAKARTA TIMUR - M.Apriansyah; Widia Astuti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study was to determine the effect of work motivation and work discipline on employee performance at PT Adhi Karya East Jakarta Building Department. The method used is quantitative method. The sampling technique used saturated sampling, which was 70 respondents. Data analysis uses validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of this study indicate that work motivation has a significant positive effect on employee performance with a regression coefficient value of 0.754 and a coefficient of determination of 41.2%. Hypothesis testing shows t count> t table or (6.903> 1.995). Work discipline also has a significant positive effect on employee performance with a regression coefficient value of 0.861 and a coefficient of determination of 53.3%. Hypothesis testing shows t count> t table or (8,809> 1,995). Simultaneously, work motivation and work discipline have a significant effect on employee performance with the regression equation Y = -8.238 + 0.535X₁ + 0.690X₂. The correlation coefficient value is 0.848 and the coefficient of determination is 71.9%, while the remaining 28.1% is influenced by other factors outside this study. The F test results show F count> F table or (85.651> 3.13).